PENERAPAN SANKSI TERHADAP NARAPIDANA YANG MELARIKAN DIRI DARI LEMBAGA PEMASYARAKATAN SAAT MENJALANI PERAWATAN DI RUMAH SAKIT: STUDI KASUS DI LAPAS KLAS II A BAUBAU - La Ode, Ali Mustafa; Susanto, Adelia; La Ode, Abdul Hamid (Jurnal Ilmu Hukum Kanturuna Wolio, 2025)
This study discusses the application of sanctions against prisoners who escape from correctional institutions while undergoing treatment in hospitals. The phenomenon of prison escapes during medical treatment poses a serious challenge for the correctional system in maintaining security and enforcing the law. This study uses a qualitative method by examining laws and regulations governing sanctions against prisoners who escape as well as case studies of several prison escape incidents. The results of the study indicate that there are gaps in supervision that are exploited by prisoners to escape, and the application of additional sanctions based on the Criminal Code (KUHP) and other related regulations still requires stricter enforcement. The sanctions applied aim to provide a deterrent effect, as well as prevent similar incidents from happening again. The conclusion of this study emphasizes the importance of increasing supervision and coordination between correctional institutions and health agencies in overseeing prisoners during treatment outside prison.